Роль німецьких антинацистських організацій у пропагандистській діяльності Радянського Союзу наприкінці Другої світової війни - Куцька, О. М.; Kutska, Olesia (Східноєвропейський національний університет імені Лесі Українки, 2017)
Проаналізовано основні мотиви кремлівського керівництва під час створення німецьких антинацистських організацій на території СРСР. Окреслено форми та способи ведення останніми пропагандистської діяльності в 1944-1945 рр. Виокремлено основні відмінності аргументів радянських органів пропаганди та антинацистських організацій.One of the directions of the German anti-Nazi movement has been analyzed - activities of the National Committee «Free Germany» and the Union of German Officers. At the same time, the study focused on the issue of the propaganda activities mainly of the organizations mentioned above at the end of the Second World War. The work defines the main stages in the creation of anti-Nazi organizations in the territory of the Soviet Union and their role in the plans of the Kremlin’s military and political leadership. , an attempt to determine the common and distinctive features in the arguments that the Soviet propagandists and supporters of the «Free Germany» movement appealed to German servicemen and the civilian population of Germany was made during analizing the features of anti - Hitler military propaganda .
The Role of German Antinacian Organizations in the Soviet Union Propaganda Activities in the end of the Second World War
Keywords: пропаганда; антинацисти; Національний комітет «Вільна Німеччина»; Союз німецьких офіцерів; Друга світова війна; propaganda; anti-Nazis; National Committee of Free Germany; Union of German Officers; World War II